The mutual influences of man-made pollutants and allergic manifestations - Prescilla V. Jeurink; Athanasios Damialis; Harry Wichers; Huub F.J. Savelkoul (Apstract: Applied Studies in Agribusiness and Commerce, 2016)
The United Nations have projected the world population to reach 9.6 billion by 2050 and that, by then, over 50% of the world population will be living in urban areas. This continuing population growth and accompanying urbanization lead to serious concerns about clean water and food for all, but also about climate change and pollution. Soil and water pollution are directly affecting the crops grown for consumption, and air pollution is affecting our mucosal barriers in the respiratory and gastro-intestinal tract on a daily basis. This review provides an overview of the different types of pollution, and the health effects triggered by especially air pollution ranging from heart disease, pulmonary disease, cancer, to fatal respiratory infections. In addition, the differences in how pollution-induced effects are affecting different age-groups are discussed. Finally, the socio-economic causes and consequences (e.g. Quality of Life and Years of Life Losses versus medical care cost) of these pollution-induced diseases are debated.